Supramolecular Self-Assembled Peptide-Based Vaccines: Current State and Future Perspectives - Abdullah, Turdimuhammad; Bhatt, Khushbu; Eggermont, Loek J.; O'Hare, Nick; Memic, Adnan; Bencherif, Sidi A. (Frontiers in Chemistry, 2020)
Despite the undeniable success of vaccination programs in preventing diseases, effective vaccines against several life-threatening infectious pathogens such as human immunodeficiency virus are still unavailable. Vaccines are designed to boost the body's natural ability to protect itself against foreign pathogens. To enhance vaccine-based immunotherapies to combat infections, cancer, and other conditions, biomaterials have been harnessed to improve vaccine safety and efficacy. Recently, peptides engineered to self-assemble into specific nanoarchitectures have shown great potential as advanced biomaterials for vaccine development. These supramolecular nanostructures (i.e., composed of many peptides) can be programmed to organize into various forms, including nanofibers, nanotubes, nanoribbons, and hydrogels. Additionally, they have been designed to be responsive upon exposure to various external stimuli, providing new innovations in the development of smart materials for vaccine delivery and immunostimulation. Specifically, self-assembled peptides can provide cell adhesion sites, epitope recognition, and antigen presentation, depending on their biochemical and structural characteristics. Furthermore, they have been tailored to form exquisite nanostructures that provide improved enzymatic stability and biocompatibility, in addition to the controlled release and targeted delivery of immunomodulatory factors (e.g., adjuvants). In this short review, we first describe the different types of self-assembled peptides and resulting nanostructures that have recently been investigated. Lastly, we discuss the recent progress and development trends of self-assembled peptide-based vaccines, their challenges, and clinical translatability, as well as their future perspectives.